SOMASCAN PROTEOMIC ASSAY: Teknologi Mutakhir dan Inovatif dalam Deteksi Dini Asbestos-Related Malignant Pleural Mesothelioma - Yemima P.; Catherine Laura Johansyah (BAPIN-ISMKI (Badan Analisis Pengembangan Ilmiah Nasional - Ikatan Senat Mahasiswa Kedokteran Indonesia), 2021)
ABSTRACT Introduction: Asbestos, as an air pollutant, is a global health problem. Asbestos exposure has been a cause of lung disease since 1930 and the number of cases continues to increase along with the use of asbestos in industry. Asbestos-Related Malignant Pleural Mesothelioma (MPM) is a primary pleural neoplasm caused by asbestos exposure, which has a high malignancy rate, and has diagnostic challenges so that the prognosis of MPM tends to be worse than other neoplasms. Therefore, an early detection is needed for high-risk groups exposed to asbestos in order to reduce the risk of morbidity and mortality from MPM. This literature study aims to review a SOMAscan Proteomic Assay tool as a cutting-edge and innovative technology for early detection of MPM. Methods: This literature was written using the literature study method using trusted search engines, such as Science Direct and PubMed. Discussion: SOMAscan Proteomic Assay (SOMALogic, Inc.; Boulder, CO, USA) is an aptamer-based multiplex proteomic technology capable of detecting protein biomarkers. This tool uses 13 types of serum-based proteins with an accuracy of 92% to detect mesothelioma cancer in high-risk populations exposed to asbestos. The sensitivity of this tool to detect MPM will be correlating even more the higher pathological stage is. Conclusion: With high accuracy in the early stages, the SOMAscan Proteomic Assay is a promising tool for early diagnosis of MPM so that it has a greater chance of successful multimodality therapy with better prognosis.